WIND SHEAR IDENTIFICATION WITH THE RETRIEVAL WIND OF DOPPLER WEARTH RADAR - S. Zhou; Y. Cui; H. Zheng; T. Zhang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
A new method, which based on the wind field retrieval algorithm of Volume Velocity Process (VVP), has been used to identified the intensity of wind shear occurred in a severe convection process in Guangzhou. The intensity of wind shear’s strength shown that new cells would be more likely to generate in areas where the magnitude generally larger than 3.0 m/(s*km). Moreover, in the areas of potential areas of rainfall, the wind shear’s strength would larger than 4.5 m/(s*km). This wind shear identify method is very helpful to forecasting severe convections’ moving and developments.